Annexion et décentrement (Altre Modernità, 2009)
Since the beginning of the twentieth century, the issue of otherness has been central in the intellectual debate among ethnologists, linguists and philosophers.  Communication can be seen as a form of translation of the Other into the language of the Self, and a parallel can indeed be established between translation and the knowledge of other peoples and cultures. As a matter of fact, in order to provide a diligent translation one has to overcome both linguistic difficulties and psychological resistances. The first eighteenth-century adventure stories and travel accounts provided biased descriptions of foreign countries and their un-European habits. The western traveler tended in fact to absorb or even force the inhabitants of other countries into his own idea of the ‘right' civilisation. A new approach towards the issue of otherness begins with the work of researchers such as Lévi-Strauss who support their knowledge of ‘other' cultures only through systematic anthropological fieldwork. Similarly, in linguistics, theorists such as Berman and Meschonnic focus on the need to know all the elements composing a text in order to perform a good translation of that text: there should be an ";intimate distance"; between the translator and his/her text, similar to the one existing, in psychoanalysis, between an analyst and his/her patient. Paul Ricœur suggests the notion of linguistic hospitality, a notion that goes beyond problems of mere understanding. And the ethno-psychotherapist Marie Rose Moro proposes an approach to the Other that considers not only the biological, but also and mostly, the psychological dimensions of the individual, with a special emphasis on the issue of difference.